Nanoscale insights into the structure of solution-processed graphene by x-ray scattering. (1st January 2023) - Yan, Zhengyu; Guimarey, María J G; Parvez, Khaled; Dun, Chaochao; Read, Oliver; Forrest, Thomas; Urban, Jeffrey J; Abdelkader, Amor; Casiraghi, Cinzia; Mirihanage, Wajira
Abstract: Chemical exfoliation is an attractive approach for the synthesis of graphene due to its low cost and simplicity. However, challenges still remain in the characterization of solution-processed graphene, in particular with atomic resolution. Through this work we demonstrate the x-ray pair distribution function as a novel approach to study solution-processed graphene or other 2D materials with atomic resolution, directly in solution, produced by liquid-phase and electrochemical exfoliations. The results show the disappearance of long-range atomic correlations, in both cases, confirming the production of single and few-layer graphene. In addition, a considerable ring distortion has been observed as compared to graphite, irrespective of the solvent used: the normal surface angle to the sheet of the powder sample should be less than 6°, compatible with ripples formation observed in suspended graphene. We attribute this effect to the interaction of solvent molecules with the graphene nanosheets.